The Category of Comparison in Latin - Pultrová, Lucie (The Language of Classical Literature, 2022)
Which Latin adjectives and adverbs allow for comparative and superlative forms, and which ones do not? Based on extensive data collection, this book aims to provide today's readers of Latin with some objective criteria for determining the answer to this question.